Using TikTok as a Marketing Media of Telemedicine X in Indonesia - Marlina Agustina Kehek; Didiek Hardiyanto Soegiantoro; Ellsya Angeline Rawar (Sean Institute, 2025)
The rapid growth of social media, particularly TikTok, has transformed digital marketing strategies across industries, including healthcare. Telemedicine X in Indonesia seeks to harness TikTok’s influence to expand outreach and enhance engagement, especially among younger demographics. However, the platform’s marketing effectiveness in this context has yet to be thoroughly evaluated. This research aims to assess the performance of Telemedicine X’s TikTok content throughout 2024 by analysing user engagement (likes and comments), content types, posting frequency, audience preferences, and consumer complaints. A descriptive-quantitative method was employed, using content analysis of all TikTok posts during the study year. Data were collected manually and processed using Microsoft Excel to quantify interactions and classify comment sentiment. The results revealed high engagement levels, with over 9 million likes and 84,000 comments, indicating significant public interest. Educational content dominated the account’s output (207 out of 228 posts), aligning with public health goals and algorithmic preferences. Promotional and drug-related content were minimal due to regulatory constraints. Complaint peaks in March and June highlighted service-related dissatisfaction, while lower volumes in other months reflected either improved service or reduced outreach. The study concludes that TikTok is a promising platform for telemedicine marketing in Indonesia, capable of driving awareness and engagement. However, it recommends more interactive content, timely customer support, and data-driven campaign optimization to strengthen brand trust and effectiveness. These findings can inform broader strategies for digital health communication in emerging markets.